The Relationships Between Governance and Risk in Brazilian Companies - Lameira, Valdir de Jesus (Review of Business Management, 2012)
This study evaluated the quality of governance practiced by a significant sample of publicly traded Brazilian companies between 2002 and 2006 and related it to their market risk. An index containing twenty questions with binary answers was used to measure governance quality. Market risk was measured by the betas, the volatility of the shares prices, the idiosyncratic risk and the weighted average cost of capital. The results obtained by the method of linear regressions were confirmed by the results obtained by structural equations. The original hypotheses that better levels of governance are associated with a lower risk were confirmed. The effects of possible endogeneity didn’t prejudice the results obtained by linear regressions. The article contributes to show how governance affects risk, which is a variable that directly affects the value of companies. Thus, knowing that governance affects the risk increases the importance to improve governance practices in companies. Key words: Governance. Risk. Publicly traded companies. Linear regressions and structural equations.